2020
DOI: 10.1039/d0cp00887g
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium-rich nanoprecipitates in calcite: atomistic mechanisms responsible for toughening in Ophiocoma wendtii

Abstract: Atomistic simulations provide insight into an example of the superiority of biogenic crystals, where Mg-rich nanoprecipitates in calcite inhibit crack propagation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…8c,d). This observation is consistent with the strengthening and toughening magnesium calcite nanoprecipitates observed in some biominerals [34][35][36].…”
Section: Molecular Dynamics Simulationssupporting
confidence: 90%
See 1 more Smart Citation
“…8c,d). This observation is consistent with the strengthening and toughening magnesium calcite nanoprecipitates observed in some biominerals [34][35][36].…”
Section: Molecular Dynamics Simulationssupporting
confidence: 90%
“…Firstly, the Mg 2+ ions are smaller than Ca 2+ and generate defects (misfits, dislocations) and lattice strain within precipitate that destabilize solid structure and lead to increased solubility and reduced solution supersaturation [1,33]. However, in some cases, Mg-rich nanoprecipitates' alignment results in strengthening and toughening the bio-carbonate matrix [34][35][36]. Secondly, because the Mg 2+ ions bind water more strongly than Ca 2+ , they introduce their hydration water into the sediment and, as a result, delay transformations to more stable and usually dehydrated carbonate polymorphs [1,[6][7][8][9][10]33].…”
Section: Introductionmentioning
confidence: 99%
“…[ 24 ] MD simulation of a nanodomain (4 nm in diameter) in calcite matrix showed a similar distribution of residual stress (Figure 16d). [ 219 ] Further MD results revealed that the presence of these Mg‐rich nanodomains significantly modifies the fracture behavior of calcite (Figure 16e). [ 219 ] In contrast to the false{101¯4false}$\{ {10\bar{1}4} \}$ cleavage fracture in pure calcite (Figure 16e‐i), the crack bisected the nanodomain along a disordered path with significant bridging (Figure 16e‐ii).…”
Section: Residual Strain/stressmentioning
confidence: 99%
“…[25][26][27][28] This is made possible by their tailored structure, that confers them toughness and optical capabilities. [26][27][28][29][30] Indeed, the DAPs contain hundreds of rounded features, called lenses, whose rounded shape guides the light through and focuses it onto photoreceptor nerve bundles. In addition, lenses's alignment along the optical c-axis of calcite minimizes birefringence.…”
Section: Introductionmentioning
confidence: 99%
“…27,29 The existence of coherent high-Mg nanoparticles and associated strains are responsible for the enhanced mechanical properties of the otherwise brittle lenses. 27,30 The crystallographic characterization of atomic structure via synchrotron High-resolution Powder X-ray Diffraction (HRPXRD) of powdered samples: the diffraction pattern displayed peaks correponding to a single low-Mg calcite phase. Upon heating, the coherent high-Mg particles grow within the lenses and lose coherency with the matrix, thereby incoherent high-Mg particles' diffraction peaks become visible by HRPXRD.…”
Section: Introductionmentioning
confidence: 99%